Flexibility for sport and fitness - Fink, Doug irector (Champaign Human Kinetics, 1997)
Flexilibity for Sport and Fitness shows toy how to assess and increase your flexibility so you'll look, feel and perform better, no matter what your sport and fitness goals.
With 1 converted disc.
Executive producer, Steven Fanizza ; writer, Tom Hanlon.
VHS format.
In English.
Keywords: Joints -- Range of motion; Physical fitness; Stretching exercises